O adolescente diante da telenovela - Elias, Maria de Fátima Faila (Comunicação & Educação, 1998)
This study aims at understanding what the participation of the soap opera, telenovela, is in the world of the teenagers. It hopes to show the importance of other socializing institutions, such as the family, society, school and friends, among others, relative to how this programming is decoded. The teenagers were surveyed both in the urban and rural areas, aiming at clarifying how the teenager, within the differentiated social contexts, positions himself when confronted with the subjected presented by the Brazilian soap opera.